Reduced Serum Levels of Soluble Interleukin-15 Receptor α in Schizophrenia and Its Relationship to the Excited Phenotype - He, Yi; Bo, Qijing; Mao, Zhen; Yang, Jian; Liu, Min; Wang, Haixia; Kastin, Abba J.; Pan, Weihong; Wang, Chuanyue; Sun, Zuoli (Frontiers in Psychiatry, 2022)
Our previous studies documented that interleukin-15 receptor α (IL-15Rα) knockout (KO) mice exhibited hyperactivity, memory impairment, and desperate behavior, which are core features of schizophrenia and depression. Due to the overlapping symptomology and pathogenesis observed for schizophrenia and depression, the present study attempted to determine whether IL-15Rα was associated with the risk of schizophrenia or depression. One hundred fifty-six participants, including 63 schizophrenia patients, 29 depressive patients, and 64 age-matched healthy controls, were enrolled in the study. We investigated the circulating levels of soluble IL-15Rα and analyzed potential links between the IL-15Rα levels and clinical symptoms present in schizophrenia or depressive patients. We observed reduced serum IL-15Rα levels in schizophrenia patients, but not depressive patients compared with controls. Moreover, a significant negative association was observed between the circulating IL-15Rα levels and excited phenotypes in the schizophrenia patients. The IL-15Rα KO mice displayed pronounced pre-pulse inhibition impairment, which was a typical symptom of schizophrenia. Interestingly, the IL-15Rα KO mice exhibited a remarkable elevation in the startle amplitude in the startle reflex test compared to wild type mice. These results demonstrated that serum levels of soluble IL-15Rα were reduced in schizophrenia and highlighted the relationship of IL-15Rα and the excited phenotype in schizophrenia patients and mice.